The effects of in-season complex contrast training on anaerobic performance metrics in elite female soccer players - Gepfert, M.; Terbalyan, A.; Roczniok, R.; Golas, A. (The Journal of Strength and Conditioning Research, 2026)
The aim of this study was to evaluate the effects of in-season complex contrast training (CCT) on speed, power, and anaerobic capacity metrics in elite female soccer players. Twenty-one players participated in a 3-phase study conducted across the postpreparatory period, midseason, and postseason. Testing included countermovement jump, single-leg jump, 5 and 30 m sprints, and the repeated anaerobic sprint test (RAST). Weekly complex training sessions combined resistance exercises with plyometric drills. Significant improvements were observed in anaerobic performance midseason compared with the preparatory phase (RAST 1, p = 0.0073, d [Cohen's d ES] = 0.45; 30 m sprint, p = 0.0073, d = 0.81), followed by performance declines at the end of the season. Peak RAST metrics improved significantly midseason (e.g., RAST 2, p = 0.025, d = 0.81; RAST 3, p = 0.0083, d = 0.95), but no changes were observed for concentric peak velocity (p = 0.98) or rate of force development (p = 0.37). The findings demonstrate that complex contrast training effectively enhances power and anaerobic performance during the midseason but may require strategic load management to mitigate late-season fatigue-related declines. A single weekly session of CCT seems sufficient to maintain, and in some instances improve, physical performance across the season. However, without a comparison group, it is unclear whether it is more or less effective than other training methods.